Effects of light quality on growth, nutritional characteristics, and antioxidant properties of winter wheat seedlings (Triticum aestivum L.) - Li, Junyan; Guo, Xiaolei; Zhang, Siqi; Zhang, Yinghua; Chen, Liping; Zheng, Wengang; Xue, Xuzhang (Frontiers in Plant Science, 2022)
Wheat seedlings are becoming popular for its high nutritional value. Effects of White (W), White + Red (WR) and White + Blue (WB) LEDs treatments on growth, nutritional characteristics and antioxidant properties of wheat seedlings were studied in a plant factory. The results showed that height, leaf area, shoot fresh and shoot dry weight per wheat seedling were the highest under WR at 13 and 22 days after planting. Soluble sugar content in leaves and stems were 22.3% and 65% respectively higher under WB than those under W. Soluble protein content in leaves and stems were 36.8% and 15.2% respectively lower under WR than those under W. Contents of total flavonoids, glutathione (GSH) and ascorbic acid (ASA) in leaves were the highest under WB, whereas malondialdehyde (MDA) content in leaves was the lowest under WB. The activities of antioxidant enzymes (SOD, POD and APX) in leaves and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging ability were also the highest under WB. In conclusion, WR promoted the growth of wheat seedlings, and WB promoted antioxidant level and nutritional accumulation. This study provides guidance for wheat seedlings to carry out preferential production (biomass or quality).